IMPLEMENTASI MEDIA DAKON-MATIKA PADA MATA KULIAH MATEMATIKA KELAS TINGGI MAHASISWA PGSD UNIVERSITAS HKBP NOMENSEN PEMATANGSIANTAR - Christa Voni R Sinaga; Apriani Sijabat; Herna Febrianty Sianipar; Theresia Siahaan (Universitas Islam Sumatera Utara, 2022)
The study carried out on the cognitive development of students, found that the ability of elementary school teacher education students at Universitas HKBP Nomensen Pematangsiantar in involving learning media still needs to be improved. Elementary school teacher education students must have the ability to use concrete objects in learning mathematics, including things related to their daily experiences. The purpose of this study was to find out how to implement the use of Dakon-matika media in high-class mathematics courses for students at the Universitas HKBP Nomensen Pematangsiantar. This research is a qualitative research with a descriptive approach with a sample of 40 students who take high grade mathematics courses. The data collection instrument used was an observation sheet on student activities in making and using Dakon-matika media. The assessment used uses a benchmark reference scoring system. As for analyzing the data obtained and answering the research questions, univariate statistical tests were used. Students are declared to have passed in the manufacture and use of Dakon-matika media if at least the student gets a score of 75. The results show that the ability of students to create and use Dakon-matika media still needs to be improved in order to meet the specified graduate learning outcomes.